Community Service Supports Coffee Cultivation and Post-Harvest in Hutabaringin Village, Sorik Marapi District, Madina - Siregar, Ameilia Zuliyanti; Tulus; Ayu, Putri Chandra; Fatimah (Piramida Akademi, 2024)
Hutabaringin Village Community, District. Sorik Merapi, Kab. Madina h sources of livelihood in the agricultural sector, namely: rice, vegetable crops, frui gelugor acid, and plantation crops, especially coffee. The problems identified ar limited capital, seeds, tools and agricultural machinery (alsintan) as well as farmer knowledge in managing coffee to obtain high productivity. Therefore, the Marsipatur Hutanabe Mono Year Service Team carries out outreach activities, training an provides donations in the form of coffee seeds and machinery in the form of mi drying houses and coffee roasting machines to support cultivation and post-harve to increase coffee productivity. This activity uses field survey methods, outreac training on controlling coffee plant pests, training on post-harvest processing coffee and focus group discussions (FGD). Next, the handover of coffee seeds, coffe drying house, coffee roasting machine and yellow trap was carried out. The activit went well and received a positive response from farmer groups in Hutabaringi Village, Puncak Sorik Marapi, Madina.